2006
DOI: 10.1016/j.freeradbiomed.2006.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Redox modulation of the hepatitis C virus replication complex is calcium dependent

Abstract: Reactive species and perturbation of the redox balance have been implicated in the pathogenesis of many viral diseases, including hepatitis C. Previously, we made a surprising discovery that concentrations of H 2 O 2 that are non-toxic to host cells disrupted hepatitis C virus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 57 publications
6
20
0
Order By: Relevance
“…In this regard, the oxidative suppression of HCV replication complex we found is highly consistent, occurring in response to H 2 O 2 , tertiary butyl hydroperoxide, extracellular generation of H 2 O 2 with glucose oxidase plus glucose, tert-butylhydroquinone, decreasing intracellular GSH content with BSO, as well as HNE [204,205] (unpublished observation). The suppression starts at concentrations as low as 0.1 µM H 2 O 2 and starts within 15 -30 min of exposure, progressively worsening by 6 hrs, and resulting in significant decreases in both the rate of HCV replication and the total viral RNA content over time.…”
Section: +supporting
confidence: 64%
See 2 more Smart Citations
“…In this regard, the oxidative suppression of HCV replication complex we found is highly consistent, occurring in response to H 2 O 2 , tertiary butyl hydroperoxide, extracellular generation of H 2 O 2 with glucose oxidase plus glucose, tert-butylhydroquinone, decreasing intracellular GSH content with BSO, as well as HNE [204,205] (unpublished observation). The suppression starts at concentrations as low as 0.1 µM H 2 O 2 and starts within 15 -30 min of exposure, progressively worsening by 6 hrs, and resulting in significant decreases in both the rate of HCV replication and the total viral RNA content over time.…”
Section: +supporting
confidence: 64%
“…human hepatoma cells, we also found that H 2 O 2 , at concentrations that did not deplete intracellular GSH or induce cell death, rapidly suppressed HCV RNA replication in a dose-dependent manner [204,205]. The suppressive effects of peroxide was comparable to those of interferon gamma and cyclosporine A, which are potent inhibitors of HCV replication [204,[206][207][208][209] (unpublished observation).…”
Section: +mentioning
confidence: 60%
See 1 more Smart Citation
“…27,28,30,31 Furthermore, NAC and VE canceled the anti-HCV activity of CsA. 31,32 Although we also examined whether NAC and VE canceled the anti-HCV activity of HA-719 in LucNeo#2 cells, they did not weaken the anti-HCV activity of HA-719 (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…Several mechanisms have been identified by which HCV infection can lead to the induction of ROS/RNS, including mitochondrial alterations (12)(13)(14)(15)(16); redistribution of calcium between the ER, cytoplasm, and mitochondria (17)(18)(19)(20)(21)(22)(23); increased expression of NADPH oxidases (24,25); enhanced expression of CYP2E1 (26 -29); as well as ER stress and the unfolded protein response (10,18,22,30,31). Oxidative stress also impacts the HCV life cycle at the level of replication and translation and can lead to viral genome heterogeneity, possibly facilitating viral escape from immune detection (32)(33)(34)(35)(36). A better understanding of the cellular events that accompany oxidative/nitrosative stress is likely to contribute to our understanding of the pathogenesis of HCV, as well as provide insight into the HCV life cycle.…”
mentioning
confidence: 99%